We rewrite the equation in standard form: x^2 + 4x - 21 = 0.
We can now use the quadratic formula:
x = (-b ± √(b^2 - 4ac)) / 2a
where a = 1, b = 4, and c = -21.
Substituting these values, we get:
x = (-4 ± √(4^2 - 4(1)(-21))) / 2(1)
x = (-4 ± √(16 + 84)) / 2
x = (-4 ± √100) / 2
We simplify the square root:
x = (-4 ± 10) / 2
There are two solutions:
x = (-4 + 10) / 2 = 3
x = (-4 - 10) / 2 = -7
Therefore, the solutions are x = 3 and x = -7.
Use the quadratic formula to solve the equation. If necessary, round to the nearest hundredth. x^2-21=-4x
1 answer